Answer:
- <u>First blank: the equation of the line that passes through A and B</u>
<u></u>
- <u>Second blank: is a solution of the equation</u>
Explanation:
Three or more points are collinear if and only if they are on the same line, and, thus they are solutions, of the same equation of the line.
When you know two points through their coordinates you can always find the equation of the line:
You can find the slope, m, of that line by using the slope formula:
- m = rise / run = Δy / Δx = (y₂ - y₁) / (x₂ - x₁)
And then, you apply the point-slope equation:
Since you know m, x₁, and y₁, your equation is determined.
Once you have your equation, substitute the x and y coordinates with the coordinates of the point C. If, and only if, the equation is satisfied, the point C is on the same line and the three points are collinear.
<span>a(b · c) = (a · b)c
answer
</span><span>associative property</span>
Circumcenter = (-1,0)
The circumcenter of a triangle is the intersection of the perpendicular bisectors of the sides of the triangle. So let's calculate a couple of the bisectors and determine their intersection.
Slope AB = (3 - -3)/(2 - -4) = (3+3)/(2+4) = 6/6 = 1
Perpendicular bisector will have a slope of -1 and will pass through point ((2-4)/2,(3-3)/2) = -2/2,0/2) = (-1,0)
Equation is of the form
y = -x + b
Substitute known point
0 = -(-1) + b
0 = 1 + b
-1 = b
So the equation for the perpendicular bisector of AB is
y = -x - 1
Now let's calculate the perpendicular bisector of BC
Slope BC = (-3 - -3)/(-4 - 2) = (-3 + 3) / (-6) = 0/-6 = 0. This means that the
line is horizontal and that the perpendicular bisector will be a vertical line with infinite slope. A point that line will pass through is ((-4 + 2)/2, (-3 + -3)/2) =
(-2/2, 0/2) = (-1,0). So the equation for the line is:
x = -1
Now we want the intersection between
x = -1 and y = -x - 1
Since we know that x has to be -1, just substitute it into the 2nd equation.
y = -x - 1
y = -(-1) - 1
y = 1 - 1
y = 0
So the circumcenter is (-1,0).
Let's verify that. The distance from the circumcenter to each vertex of the triangle will be the same. Using the Pythagorean theorem, C^2 = A^2 + B^2. We're not going to bother taking the square root since if the squares are equal, then square roots will also be equal.
Distance^2 from (2,3):
(2- -1)^2 + (3-0)^2 = 3^2 + 3^2 = 9 + 9 = 18
Distance^2 from (-4,-3):
(-4 - -1)^2 + (-3 - 0)^2 = -3^2 + -3^2 = 9 + 9 = 18
Distance^2 from (2,-3):
(2 - -1)^2 + (-3 - 0)^2 = 3^2 + -3^2 = 9 + 9 = 18
The distances to all three vertexes is identical, so (-1,0) is verified as the circumcenter.
Factor the following:
5 x^2 + 20 x + 15
Factor 5 out of 5 x^2 + 20 x + 15:
5 (x^2 + 4 x + 3)
The factors of 3 that sum to 4 are 3 and 1. So, x^2 + 4 x + 3 = (x + 3) (x + 1):
Answer: 5 (x + 3) (x + 1)